Auditoría administrativa a la fundación construyamos un sueño ubicada en la ciudad de Latacunga, en la calle Tarqui Y Sanchez De Orellana, del 1° de enero al 31 de diciembre del 2008 - Almachi Chiguano, Nelly Carlota (2010)
Management Audit was developed in the Build a Dream Foundation. It is located in Latacunga for the period January to December 2008. The investigation is orientated to measure the degree of accomplishment of the goals and objectives planned by the institution and also it attempts to determine the efficiency and effectiveness of the use of the resources and personal progress. As part of the audit is carried out by surveys, interviews and observation to diagnose the feelings of personal reference to the organization and the obtained data are correct and reliable. After development of the Management Audit in each one of its phases we analyzed the information and findings to determine an approach to management analysis and give solutions to redesign the processes that were not complete. After the Management Audit, we propose various conclusions and recommendations through which we try to highlight the most important parts of the investigation.